Dolphin girl. 1, Trouble in pizza paradise! - Smith, Zach (Pixel + Ink, 2020)
"In small-town Deerburbia, young superhero Dolphin Girl and her dad, Captain Dugong, run a popular tropical-themed restaurant. Pizza Paradise! also doubles as their hideout. And danger is never far away! One day, while Dad is training Dolphin Girl in signature moves (Blowhole cannon! Extreme breath holding!), they get word that their rivals are up to no good. It's time to swim into action! But when Captain Dugong flakes on Dolphin Girl, she must summon her inner sea mammal and flip the situation. Recruiting gamemaster Keith to help, Dolphin Girl sets out to battle the evil Sea Cow and save Pizza Paradise!"--Provided by publisher.